Coexpression of GMP-140 and PAF by endothelium stimulated by histamine or thrombin: a juxtacrine system for adhesion and activation of neutrophils (The Rockefeller University Press, 1991)
The adhesion of polymorphonuclear leukocytes (PMNs) to vascular endothelial cells (EC) is an early and fundamental event in acute inflammation. This process requires the regulated expression of molecules on both the EC and PMN. EC stimulated with histamine or thrombin coexpress two proadhesive molecules within minutes: granule membrane protein 140 (GMP-140), a member of the selectin family, and platelet-activating factor (PAF), a biologically active phospholipid. Coexpression of GMP-140 and PAF is required for maximal PMN adhesion and the two molecules act in a cooperative fashion. The component of adhesion mediated by EC-associated PAF requires activation of CD11/CD18 integrins on the PMN and binding of these heterodimers to counterreceptors on the EC. GMP-140 also binds to a receptor on the PMN; however, it tethers the PMN to the EC without requiring activation of CD11/CD18 integrins. This component of the adhesive interaction is blocked by antibodies to GMP-140 or by GMP-140 in the fluid phase. Experiments with purified GMP-140 indicate that binding to its receptor on the PMN does not directly induce PMN adhesiveness but that it potentiates the CD11/CD18-dependent adhesive response to PAF by a mechanism that involves events distal to the PAF receptor. Tethering of the PMN to the EC by GMP-140 may also be required for efficient interaction of PAF with its receptor on the PMN. These observations define a complex cell recognition system in which tethering of PMNs by a selectin, GMP-140, facilitates juxtacrine activation of the leukocytes by a signaling molecule, PAF. The latter event recruits the third component of the adhesive interaction, the CD11/CD18 integrins.